Verify the following:

(a) 18 ×[7+(-3)] = [18 × 7] + [18 × (-3)]


(b) (-21) ×[(-4)+(-6)] = [(-21) ×(-4)] + [(-21) ×(-6)]

(a) We have,


L.H.S = 18 × [7 + (- 3)]


= 18 × [7 – 3]


= 18 × [4]


= 72


Also, we have:


R.H.S = [18 × 7] + [18 × (-3)]


= 126 + (-54)


= 72


Therefore,


L.H.S = R.H.S


Hence,


18 × [7 + (- 3)] = [18 × 7] + [18 × (-3)]


(b) We have,


L.H.S = (-21) × [(-4) + (-6)]


= (-21) × [- 4 – 6]


= (-21) × (-10)


= 210


Also, we have:


L.H.S = [(-21) × (-4) + [(-21) × (-6)]


= 84 + 126


= 210


Also, we have:


R.H.S = [(-21) × (-4)] + [(-21) × (-6)]


= 84 + 126


= 210


Therefore,


L.H.S = R.H.S


Hence,


[(-21) × (-4) + [(-21) × (-6)] = [(-21) × (-4)] + [(-21) × (-6)]


11